Finite Mixture Estimation of Multiproduct Cost Functions - Beard, T. Randolph; Caudill, Steven B.; Gropper, Daniel M. (The Review of Economics and Statistics, 1991)
This paper presents a technique of cost-function estimation, based on the theory of finite mixture distributions, which allows for the simultaneous existence of multiple technologies of production when the researcher does not know which observations correspond to which technologies. The finite mixture technique provides estimates of the proportions of firms using the various technologies, facilitates comparisons between technologies, and preserves the traditional interpretations of cost estimation. After describing the mixture procedure, the technique is illustrated on a large sample of savings and loan associations, and it is concluded that this industry exhibits multiple technologies of production. Copyright 1991 by MIT Press.